2017
DOI: 10.5296/jpag.v7i4.11972
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Public Education Expenditures: An Empirical Analysis of Changing Patterns and Growth of Public Expenditure on Education in Kenya

Abstract: This paper examined several factors that affect growth of public expenditure on education sector using reputable theories of public policy analysis, economics, and public finance. These theories were used to test and examine these factors mainly for the purposes of providing public policy recommendations. Standard multiple linear regression analysis method was used to analyze factors affecting growth of public expenditure on education using the four formulated models and equations representing; general educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…The result from this study further reported that inflation rate (INF) was positively significant to the government education spending. Our result was consistent with Imana (2017) that demonstrated inflation rate with a positive effect on public education expenditure. High inflation rate causes prices hike of commodities and services, thus making parents unable to afford tertiary education fees and other education costs.…”
Section: Estimation Results Based On Ardl Bound Testing Approachsupporting
confidence: 93%
“…The result from this study further reported that inflation rate (INF) was positively significant to the government education spending. Our result was consistent with Imana (2017) that demonstrated inflation rate with a positive effect on public education expenditure. High inflation rate causes prices hike of commodities and services, thus making parents unable to afford tertiary education fees and other education costs.…”
Section: Estimation Results Based On Ardl Bound Testing Approachsupporting
confidence: 93%
“…On the other hand, the result reported that inflation rate (INF) was positively significant in the long run. Our result supported finding by Imana (2017) that inflation rate had a positive effect on education expenditure. High inflation rate causes prices hike of commodities and services, thus making parents unable to afford high school fees and other education costs.…”
Section: Estimation Results Based On Ardl Bound Testing Approachsupporting
confidence: 92%
“…The government of Kenya has devolved treasury management to county governments in tandem with the theory of fiscal federalism which advocates for regional governments which are closer to the citizens. The government has made several reforms including the public finance management reforms as enablers of the devolved treasury management towards implementation of the Constitution of Kenya 2010 which introduced the 47 County governments and the National government in Kenya (Imana, 2017). Roberts (2013), assert that generally treasury management was concentrated on Working Capital management which became more evident during the 1992/93 World Financial crisis.…”
Section: Introductionmentioning
confidence: 99%